Growth behavior of publications and patents: A comparative study on selected Asian economies - Wong, Chan-Yuan; Goh, Kim-Leng (Elsevier, 2010)
This study attempts to model the growth behavior of the number of publications and patents of South Korea, Taiwan, Japan and Malaysia. Three competing growth functions, namely, simple logistic growth function, bi-logistic growth function and logistic function within a dynamic carrying capacity were considered. The findings provide insight to the diffusion process of science and technology, often measured by the number of publications and patents, respectively. The function that provides the best fit to the observed data was opted for explaining the diffusion process. The function with the best fit is the bi-logistic growth function for the number of publications as well as the number of patents of South Korea and Taiwan, the logistic growth function within a dynamic carrying capacity (LGDCC) for the number of publications and the bi-logistic growth function for the number of patents of Japan, and the LGDCC for the number of publications and simple growth function for the number of patents of Malaysia. The results suggest a dynamic self-propagating growth for the science and technology, and thereby a transition from science and technology-push to market-pull growth for South Korea and Taiwan. While a similar transition was observed for the technology of Japan, the growth in science had entered a maturity stage. On the other hand, the growth potential in science is dynamic for Malaysia, but its technological advancement is relatively lower and static compared to the other economies. (C) 2010 Elsevier Ltd. All rights reserved.